2001
DOI: 10.1016/s0378-1097(01)00455-4
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Mycobacterium tuberculosis secreted antigen SA-5K in intracellular survival of recombinant Mycobacterium smegmatis

Abstract: A new protein (SA-5K) secreted in culture filtrates by Mycobacterium bovis, Mycobacterium tuberculosis, and few other mycobacterial species was previously identified and purified in our laboratory. In order to evaluate the putative role of SA-5K during intracellular mycobacterial growth, in the present study the SA-5K gene was cloned and expressed in Mycobacterium smegmatis, a rapid growing nonpathogenic mycobacterium which does not contain the gene for the protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Mycobacterial cultures and antigen preparations BCG (Pasteur Merieux, Lyon, France) was grown in rolling bottles in modified Sauton's medium enriched with 0AE5% sodium pyruvate and 0AE5% glucose. 26 Bacteria were harvested in the logarithmic growth phase, washed by centrifugation and resuspended in phosphate-buffered saline (PBS) at 5 · 10 7 colony-forming units (CFU)/ml. Aliquots were stored frozen at )70°until use.…”
Section: Methodsmentioning
confidence: 99%
“…Mycobacterial cultures and antigen preparations BCG (Pasteur Merieux, Lyon, France) was grown in rolling bottles in modified Sauton's medium enriched with 0AE5% sodium pyruvate and 0AE5% glucose. 26 Bacteria were harvested in the logarithmic growth phase, washed by centrifugation and resuspended in phosphate-buffered saline (PBS) at 5 · 10 7 colony-forming units (CFU)/ml. Aliquots were stored frozen at )70°until use.…”
Section: Methodsmentioning
confidence: 99%
“…Similar results were obtained when the stimulatory effect on growth was evaluated on small inocula of fresh cultures of BCG using the MPN. Previous studies in our laboratory have demonstrated that the expression of the M. tuberculosis TB8.4 gene in M. smegmatis (a fast-growing non-pathogenic mycobacterium that does not contain the gene for the protein) was associated with a higher level of intracellular growth of recombinant M. smegmatis compared to the vector control strain [9]. On the other hand, disruption of the BCG TB8.4 homolog caused an impaired ability of the knock-out BCG strain to grow within human macrophages compared to wild-type and complemented strains [12], suggesting a role for the corresponding protein in intracellular growth/survival mechanisms of mycobacteria.…”
Section: Discussionmentioning
confidence: 95%
“…Culture and activation of THP‐1 cells were carried out as previously described [6]. BCG was added to the cells at a multiplicity of infection of 1:10 (bacteria:cells).…”
Section: Methodsmentioning
confidence: 99%
“…Over the last few years several efforts have been made to identify mycobacterial genes specifically expressed or induced inside human macrophages cultured in vitro and a number of proteins involved in intracellular survival have been described [3–9]. In contrast, very little is yet known about the genes and the corresponding protein products required by M. tuberculosis for growth in the human host [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation